An Overview of Commonly Used Natural Alternatives for the Treatment of Androgenetic Alopecia, with Special Emphasis on Rosemary Oil - Bin Rubaian NF; Alzamami HFA; Amir BA (Dove Medical Press, 2024)
Nouf F Bin Rubaian,1 Haya Fahad Abdulaziz Alzamami,1 Baraa Abdulrazack Amir2 1Dermatology Department of King Fahad Hospital of the University, Imam Abdulrahman Bin Faisal University, Al Khobar, Saudi Arabia; 2College of Medicine, Department of Medicine, Imam Abdulrahman Bin Faisal University, Al Khobar, Saudi ArabiaCorrespondence: Baraa Abdulrazack Amir, College of Medicine, Department of Medicine, Imam Abdulrahman bin Faisal University, 95HV+V3M, King Faisal Ibn Abd Al Aziz, Al Safa, Al Khobar, 34224, Saudi Arabia, Tel +00966 546254326, Email bamir2699@gmail.comAbstract: Androgenetic alopecia is a chronic dermatological condition in which genetically predisposed individuals undergo progressive hair loss secondary to the effects of circulating androgens. It has been well documented that dihydrotestosterone binds to the androgenic receptors prevalent in the scalp, thus inducing miniaturization of the hair follicle. To date, the only FDA approved medications for the treatment of androgenetic alopecia are finasteride and minoxidil. A plethora of studies have been conducted testing the efficacy of various herbal compounds, but additional research is needed to further establish the concrete efficacy of such natural remedies in treating androgenetic alopecia. Of late, rosemary oil has gained mass popularity as a promising natural alternative. This review article will not only provide a detailed background on this ancient herbal component but will additionally overview all other major herbal alternatives including peppermint oil, tea tree oil, green tea, pumpkin seed oil, saw palmetto, and lavender oil and will summarize the latest clinical studies, which have tested their efficacy for the management of androgenetic alopecia.Keywords: androgenetic alopecia, alopecia, rosemary, Rosmarinus officinalis, natural, hair